A Digital Topographic Model of the Lunar North Pole Area Derived from Galileo SSI Multi-Look Angle Images - Oberst, J. (1995)
49 Galileo SSI green filter multi-look angle images obtained from distances of between 115 000 km and 145 000 km, during Earth/Moon encounter in December 199, were analyzed to derive topographic modelsof the lunar north pole area. The procedure is based upon automatic digital image matching followed by object point determination using ray intersection methods. Nominal camera pointing data were correctedusing recent lunar control point network information and photogrammetric bundle-block adjustment techniques. The terrain modelcovers part of an area on the Earth-facing hemisphere, extending from the lunar equator to 80 deg North at a grid spacing of 2.5 km and a height precision of approximately 500 m. The Clementine Laser Altimeter Data (LIDAR) is limited to latitudes lower than 75 deg. Hence, this new terrain model extendsthe available topographic data for the Moon further to the north. The model is equivalent in grid spacing to the 2x2 degree global elevation data set derived from LIDAR at northern latitudes, but it has up to twice as good spatial resolution of the CLementine model nearer the equator. The terrain model shows the impact basins Humboldt, Serenitatis, Crisium, and Imbrium. Morpholoic studies and comparison with the Galileo multispectraldata of these prominent lunar basins can be made. The techniques demonstrated here will be used in the analysis of Galileo images that will be obtained during the Jupiter orbit beginning next year.